THU0143 EFFECT OF RITUXIMAB OR TUMOUR NECROSIS FACTOR INHIBITORS ON LUNG INFECTION AND 5-YEAR SURVIVAL IN RHEUMATOID ARTHRITIS-ASSOCIATED BRONCHIECTASIS. (2nd June 2020) - MD Yusof, M. Y.; Iqbal, K.; Darby, M.; Lettieri, G.; Vital, E.; Beirne, P.; Dass, S.; Emery, P.; Kelly, C.
Abstract : Background: Bronchiectasis (BR) is a significant pulmonary morbidity common in people with rheumatoid arthritis (RA). Patients with RA and bronchiectasis (RA-BR) often have severe arthritis but the use of biologics may be difficult in this group of patient due to concerns over safety. There is no data comparing the use of rituximab (RTX) and tumour necrosis factor inhibitors (TNFi) in RA-BR. Objectives: To evaluate the effect of RTX in patients with RA-BR and compare 5-year respiratory survival between those treated with RTX and TNFi. Methods: A retrospective observational cohort study of RA-BR was conducted in RTX or TNFi-treated RA patients from two UK centres over 10 years. BR was assessed using number of infective exacerbations/year. Respiratory survival was defined as time from therapy initiation to discontinuation either due to lung exacerbation or lung-related deaths. Results: Of 800 RTX-treated RA patients, 68 had RA-BR (prevalence 8.5%). Post-RTX, new BR was diagnosed in 3/735 patients (incidence 0.4%). At 12 months post-Cycle 1 RTX, 21/68 (31%) patients had fewer exacerbations than the year pre-RTX, 36/68 (53%) remained stable and 11/68 (16%) had increased exacerbations. In multivariable analysis, a factor associated with increased risk of this initial exacerbation was pseudomonas colonisation [OR 7.23 (95% CI 1.28-40.80)] while older age reduced risk [OR 0.44 (95% CI 0.21-0.90) per 10 years of age]. The rates of exacerbation improved after Cycle 2 RTX and stabilised up to 5 cycles. Of patients who received ≥2 RTX cycles (n=60), increased exacerbations occurred in 7/60 (12%) and were associated with low IgG, aspergillosis and concurrent alpha-1-antitrypsin deficiency. Respiratory survival was compared between RA-BR patients treated with RTX (N=68) or TNFi (N=46). Most characteristics were matched but median (IQR) number of infective exacerbations/year in the previous 12 months pre-bDMARDs was higher in those treated with RTX than TNFi; 3.0 (1-4) and 0 (0-2) respectively. Overall, 8/68 (11.8%) patients discontinued RTX while 15/46 (32.6%) discontinued TNFi due to respiratory causes. The adjusted 5-year respiratory survival was better in RTX-treated compared to TNFi-treated RA-BR patients; HR 0.40 (95% CI 0.17–0.96); p=0.041. Conclusion: The majority RA-BR patients had stable or improved pulmonary symptoms during RTX therapy over a prolonged follow-up period. In isolated cases, worsening of exacerbation after RTX therapy had definable causes. Despite a higher rate of exacerbations pre-biologic, rates of discontinuation due to adverse lung outcomes were better for RTX than a matched TNFi cohort. RTX appears to be an acceptable therapeutic choice for RA-BR if a biologic is needed. Disclosure of Interests: Md Yuzaiful Md Yusof: None declared, Kundan Iqbal: None declared, Michael Darby: None declared, Giovanni Lettieri: None declared, Edward Vital Grant/research support from: AstraZeneca, Roche/Genentech, and Sandoz, Consultant of: AstraZeneca, GSK, Roche/Genentech, and Sandoz, Speakers bureau: Becton Dickinson and GSK, Paul Beirne: None declared, Shouvik Dass Grant/research support from: Roche and GSK, Paul Emery Grant/research support from: AbbVie, Bristol-Myers Squibb, Merck Sharp & Dohme, Pfizer, Roche (all paid to employer), Consultant of: AbbVie (consultant, clinical trials, advisor), Bristol-Myers Squibb (consultant, clinical trials, advisor), Lilly (clinical trials, advisor), Merck Sharp & Dohme (consultant, clinical trials, advisor), Novartis (consultant, clinical trials, advisor), Pfizer (consultant, clinical trials, advisor), Roche (consultant, clinical trials, advisor), Samsung (clinical trials, advisor), Sandoz (clinical trials, advisor), UCB (consultant, clinical trials, advisor), Clive Kelly Consultant of: Boehringer Ingelheim, Speakers bureau: Boehringer Ingelheim